1984
DOI: 10.1007/bf01951922
|View full text |Cite
|
Sign up to set email alerts
|

Aldose metabolism in developing human fetal brain and liver

Abstract: Aldose reductase, sorbitol dehydrogenase, and glucose-6-phosphate dehydrogenase enzyme activities were studied in human foetal brain and liver at different periods of gestation. Aldose reductase activity in liver disappears after 16 weeks of gestation whereas sorbitol dehydrogenase keeps on increasing in liver as well as in brain. In utero, some glucose metabolism may be mediated through an active sorbitol pathway in human fetuses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…However, these data are inconsistent with data showing that sheep placenta expresses high levels of aldose reductase, but not sorbitol dehydrogenase [ 31 , 32 ]. Regardless, given that sorbitol dehydrogenase is known to be present in human fetal liver and brain [ 33 ], our findings raise the intriguing possibility that the sorbitol generated by the placenta could still be a substrate for fetal fructose production, which may have important ramifications for the developing fetal brain. Furthermore, because our samples were collected in the absence of labor, they may be a more accurate reflection of fetal exposure as it has been shown that stress from labor induces higher cord blood levels of glucose and fructose compared to levels obtained in the absence of labor [ 34 ].…”
Section: Discussionmentioning
confidence: 86%
“…However, these data are inconsistent with data showing that sheep placenta expresses high levels of aldose reductase, but not sorbitol dehydrogenase [ 31 , 32 ]. Regardless, given that sorbitol dehydrogenase is known to be present in human fetal liver and brain [ 33 ], our findings raise the intriguing possibility that the sorbitol generated by the placenta could still be a substrate for fetal fructose production, which may have important ramifications for the developing fetal brain. Furthermore, because our samples were collected in the absence of labor, they may be a more accurate reflection of fetal exposure as it has been shown that stress from labor induces higher cord blood levels of glucose and fructose compared to levels obtained in the absence of labor [ 34 ].…”
Section: Discussionmentioning
confidence: 86%
“…During embryonic development AR plays an important role in the liver to reduce carbohydrates. Increased expression of AR in the fetal liver up to 16 th week of gestation and disappearance at later stages suggests that in normal adult liver AR is not required [82]. However, AR is reexpressed with functionally active enzyme in response to the loss or reduction of activity of various glycolytic enzymes and increased proliferative activity during hepatocarcinogenesis [83].…”
Section: Role Of Ar In Carcinogenesismentioning
confidence: 99%
“…In the liver, AR was found to be transiently expressed during embryogenesis [ 3 ]. In adult animals, hepatic AR expression or activity is barely detectable or absent [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the liver, AR was found to be transiently expressed during embryogenesis [ 3 ]. In adult animals, hepatic AR expression or activity is barely detectable or absent [ 3 , 4 ]. A number of recent studies, nonetheless, have shown that hepatic AR can be significantly induced and activated under a variety of stress conditions or in diseased livers.…”
Section: Introductionmentioning
confidence: 99%